2013
DOI: 10.1055/s-0032-1326225
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided celiac ganglia neurolysis vs. celiac plexus neurolysis: a randomized multicenter trial

Abstract: http://www.umin.ac.jp/ctr/index.htm (ID: UMIN-000002536).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
96
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(97 citation statements)
references
References 19 publications
0
96
0
1
Order By: Relevance
“…EUS-CGN resulted in superior reductions in pain scores (25 of 34 cases) compared with EUS-CPN (15 of 33 patients; P = 0.026). 110 Furthermore, CGN achieved total pain relief in 50% patients, relative to 18.2% in CPN arm (P = 0.01) with number needed to treat (NNT) of 3. 110 Complications from CGN in both studies were minimal and similar to those observed with CPN, including but not limited to diarrhea, hypotension, bleeding at puncture site, and abdominal pain.…”
Section: Eus-guided Anastomosismentioning
confidence: 95%
See 2 more Smart Citations
“…EUS-CGN resulted in superior reductions in pain scores (25 of 34 cases) compared with EUS-CPN (15 of 33 patients; P = 0.026). 110 Furthermore, CGN achieved total pain relief in 50% patients, relative to 18.2% in CPN arm (P = 0.01) with number needed to treat (NNT) of 3. 110 Complications from CGN in both studies were minimal and similar to those observed with CPN, including but not limited to diarrhea, hypotension, bleeding at puncture site, and abdominal pain.…”
Section: Eus-guided Anastomosismentioning
confidence: 95%
“…110 Furthermore, CGN achieved total pain relief in 50% patients, relative to 18.2% in CPN arm (P = 0.01) with number needed to treat (NNT) of 3. 110 Complications from CGN in both studies were minimal and similar to those observed with CPN, including but not limited to diarrhea, hypotension, bleeding at puncture site, and abdominal pain. 3,4,6,109,110 Discussion EUS with FNA remains an exceedingly accurate method in diagnosing and staging pancreatic cancer.…”
Section: Eus-guided Anastomosismentioning
confidence: 95%
See 1 more Smart Citation
“…48 A randomized control trial comparing the EUS-CPN versus EUS-CGN showed that the endoscopist could visualize the celiac ganglia by EUS in 88% of cases and EUS-CGN had a better response rate (75.5%) when compared to standard EUS-CPN (45.5%). 49 A recent study evaluating this technique with more detail, showed that celiac plexus ganglia could be visualized by EUS most the times and that the spread of ethanol using EUS-CGN (high volume, 4 mL per ganglion) resulted in a large and bilateral spread of ethanol comparable to the standard EUS-CPN technique. The authors hypothesize that the increased clinical effect of EUS-CGN compared to EUS-CPN could be because the ganglion are affected from the inside out as well as from the outside in.…”
Section: Targeting the Celiac Plexus For The Treatment Of Chronic Painmentioning
confidence: 99%
“…At this moment, EUS is an increasing reference for a range of therapeutic procedures with specific complications risk, as drainage of pancreatic pseudocysts, abscess and necrosis debridement [82,83], celiac plexus neurolysis [84], biliary drainage [85], or even research vascular procedures [86].…”
Section: Endoscopic Ultrasound (Eus)mentioning
confidence: 99%